Large-Eddy Simulation (LES) on the Square and Triangular Tall Buildings to Measure Drag Force. (26th May 2021) - Daemei, Abdollah B.; Darvish, Amiraslan; Aeinehvand, Roya; Razzaghipour, Amirali
Abstract : The wind load issues play a significant role in designing tall buildings, which has sometimes been considered an even more essential factor than earthquake loads. Also, investigating wind behavior in tall buildings is a crucial issue in architectural and structural design. A primary concern of wind engineering and aerodynamics is drag force. Drag force refers to a solid object's behavior in the relative wind flow velocity direction in terms of fluid dynamics. The investigation involved only drag forces. The Autodesk Flow Design 2014 software was utilized as a wind tunnel simulator. The Large Eddy Simulation (LES) method was used for turbulence solving. This study aims to optimize tall square and triangular-shaped buildings in order to reduce drag force under along-wind motion. For this purpose, architectural aerodynamic strategies such as chamfered, rounded, and recessed corners were applied as aerodynamic modifications. Moreover, aerodynamic forms, including tapering and setting back on shapes, were applied on 24 building models. Generally, the height ( H ) and breadth ( b ) ratios were set to H : 200  m, which is equivalent to almost 60 stories, and b: 25  m wide. The obtained results indicate that model S5 (with a square floor plan) achieved 0.65 C D, and the t1 (with a triangular floor plan) achieved 0.30 C D, which could provide the best building model to reduce drag force. In this regard, the s1 could perform over 50% better in reducing wind load. Concerning the aerodynamic modification performance, the simulation results indicate that these modifications were able to lead to over 50% better performance in reducing wind force in square samples compared to triangular samples.